2015
DOI: 10.1007/s13277-015-3647-0
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 is a potential marker of tumor-initiating cells in breast cancer

Abstract: The existence of tumor-initiating cells (TICs) within solid tumors has been hypothesized to explain tumor heterogeneity and resistance to cancer therapy. In breast cancer, the expression of CD44 and CD24 and the activity of aldehyde dehydrogenase 1 (ALDH1) can be used to selectively isolate a cell population enriched in TICs. However, the ideal marker to identify TICs has not been established. The aim of this study was to evaluate the expression of novel potential markers for TIC in breast carcinoma. We prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Recent evidence has shown that the ABC family of transporters is associated with CSCs. 25, 26, 27, 28 Thus, we also detected their expression when NMI was knocked down. The results showed that knockdown of NMI led to the increased expression of ABC transporter genes such as ABCG2 and ABCB1 (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…Recent evidence has shown that the ABC family of transporters is associated with CSCs. 25, 26, 27, 28 Thus, we also detected their expression when NMI was knocked down. The results showed that knockdown of NMI led to the increased expression of ABC transporter genes such as ABCG2 and ABCB1 (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 98%
“…110 These cells also have intrinsic mechanisms for chemoresistance, such as upregulation of drug transporters, including the breast cancer resistance protein (also known as ABCG 2 ). 111 By evading the standard chemotherapeutic treatments, it is thought that the CSCs are also responsible for the relapse experienced in many cancers, especially TNBCs. 112 Studies have also shown that these cells are a main contributor to metastasis, and are able to initiate solid tumor formation when xenotransplanted at low cell densities.…”
Section: Breast Cancer Subtypesmentioning
confidence: 99%
“…αSMA ×400 A B and TIMP2 to maintain the balance of extracellular matrix, which is usually disrupted after activation in pancreatitis and PDAC. Several in vitro and in vivo studies suggest that PSCs may have progenitor-like capabilities, possessing ATP-binding cassette G2 (ABCG2) and they transform into insulin-secreting cells upon exposure to the relevant culture medium (40,(43)(44)(45)(46).…”
Section: Sirius Red ×200mentioning
confidence: 99%